An epidemic of Mycoplasma pneumoniae in Manitoba: A Serological Report - Laila Sekla; Walter Stackiw; Gudrun Eibisch; Donna Kolton (Canadian Journal of Infectious Diseases)
Objectives: To report an epidemic of Mycoplasma pneumoniae in Manitoba and to discuss the limitations of the serodiagnostic tests used.